Skip to main content

3.10 Linearization and Multivariate Taylor Series

The gradient $\triangledown f$ of a function $f$ is often used for a locally linear approximation of $f$ around $x_0$.
$f(x) \approx f(x_0)+(\bigtriangledown_xf)(x_0)(x-x_0)$

Here $(\bigtriangledown_xf)(x_0)$ is the gradient of $f$ with respect to $x$, evaluated at $x_0$.
The following Figure illustrates the linear approximation of a function $f$ at an input $x_0$. The original function is approximated by a straight line.This approximation is locally accurate, but the farther we move away from $x_0$, the worse the approximation gets.This is a special case of multivariate Taylor series expansion of $f$ at $x_0$, where we consider only the first two terms.




Multivariate Taylor Series: Definition
We consider a function
$f:\mathbb{R}^D \to \mathbb{R}$
$x \to f(x), \quad x \in \mathbb{R}^D$
that is smooth at $x_0$. When we define the difference vector $\delta= x- x_0$, the multivariate Taylor series of $f$ at $x_0$ is defined as

$f(x)=\sum_{k=0}^{\infty } \frac{D_x^kf(x_0)}{k!} \delta^k$
where $D^k_xf(x_0)$ is the $k-th$ derivative of $f$ with respect to $x$, evaluated at $x_0$.

Taylor Polynomial: Definition
The Taylor polynomial of degree $n$ of $f$ at $x_0$ contains the first $n+1$ components of the Taylor series and is defined as
$T_n(x)=\sum_{k=0}^{n } \frac{D_x^kf(x_0)}{k!} \delta^k$

Note that both $D_x^kf$ and $\delta^k$ are $k-th$ order tensors.i.e., $k$ dimensional arrays. The $k$th order tensor $\delta^k \in \mathbb{R}^{D \times D \times \ldots \times D}$ is obtained as a $k$ fold outer product denoted by $\bigotimes$, of the vector $\delta \in \mathbb{R}^D$. For example

$\delta^2=\delta \bigotimes \delta=\delta \delta^T,\quad \delta^2[i,j]=\delta[i][\delta[j]$

In general we obtain the terms
$D_x^kf(x_0)\delta^k=\sum_{i_1=1}^D\cdots\sum_{i_k=1}^DD_x^kf(x_0)[i_1,\ldots,i_k]\delta[i_1]\cdots\delta[i_k]$

Lets write down the first few terms of $D_x^kf(x_0)\delta^k$ of the Taylor Series expansion for $k=0,\ldots,3$ and $\delta=x-x_0$.


Example: ( university question)
Consider the function $f(x,y)=x^2+2xy+y^3$. Find the Taylor series expansion of  $f$ at $(x_0,y_0)=(1,2)$
Note that we are looking for a Taylor series expansion, which itself is a linear combination of Polynomials.To express the polynomial of degree 3 , the Taylor series expansion must contain terms of 4th or higher order.

$f(1,2)=13$
$\frac{\partial f}{\partial x}=2x+2y=\frac{\partial f}{\partial x}(1,2)=6$
$\frac{\partial f}{\partial y}=2x+3y^2=\frac{\partial f}{\partial y}(1,2)=14$
Therefore we obtain
$D_{x,y}^1f(1,2)=\bigtriangledown_{x,y}f(1,2)=\left[ \frac{\partial f}{\partial x} \quad \frac{\partial f}{\partial y}\right]=[6 \quad 14] \in \mathbb{R}^{1 \times 2}$

$\frac{D_{x,y}^1f(1,2)}{1!}\delta=\left[6 \quad 14 \right]\begin{bmatrix}
x-1\\
y-2\end{bmatrix}=6(x-1)+14(y-2)$

Note that this contains only linear terms.i.e., first-order polynomials.
The second order partial derivatives are given by
 $\frac{\partial^2 f}{\partial x^2}=2 \Rightarrow \frac{\partial^2 f}{\partial x^2}(1,2)=2$
 $\frac{\partial^2 f}{\partial y^2}=6y \Rightarrow \frac{\partial^2 f}{\partial y^2}(1,2)=12$
 $\frac{\partial^2 f}{\partial y \partial x}=2 \Rightarrow \frac{\partial^2 f}{\partial y \partial x}(1,2)=2$
$\frac{\partial^2 f}{\partial x \partial y}=2 \Rightarrow \frac{\partial^2 f}{\partial x \partial y}(1,2)=2$

$H=\begin{bmatrix}
2 & 2\\
2& 6y
\end{bmatrix} \in \mathbb{R}^{2 \times 2}$

So the Hessian at $(1,2)$ is
$H(1,2)=\begin{bmatrix}
2 & 2\\
2& 12
\end{bmatrix} \in \mathbb{R}^{2 \times 2}$

Therefore the next term of the Taylor series expansion is given by
$\frac{D_{x,y}^2f(1,2)}{2!}\delta^2=\frac{1}{2}\delta^TH(1,2)\delta$
$\quad=\frac{1}{2}\begin{bmatrix}
x-1 & y-2
\end{bmatrix}\begin{bmatrix}
2 & 2\\
2& 12
\end{bmatrix} \begin{bmatrix}
x-1\\
y-2
\end{bmatrix}$
$=(x-1)^2+2(x-1)(y-2)+6(y-2)^2$
This is a second order polynomial

The third order derivatives are obtained as
$D^3_{x,y}f=\left[ \frac{\partial H}{\partial x}\quad \frac{\partial H}{\partial y}\right] \in \mathbb{R}^{2 \times 2 \times 2}$

$D^3_{x,y}f[:,:,1]=\frac{\partial H}{\partial x}=\begin{bmatrix}
\frac{\partial ^3f}{\partial x^3} & \frac{\partial ^3f}{\partial x^2 \partial y}\\
\frac{\partial ^3f}{\partial x \partial y \partial x}& \frac{\partial ^3f}{\partial x\partial y^2}
\end{bmatrix}$


$D^3_{x,y}f[:,:,2]=\frac{\partial H}{\partial y}=\begin{bmatrix}
\frac{\partial ^3f}{\partial y \partial x^2} & \frac{\partial ^3f}{\partial y \partial x \partial y}\\
\frac{\partial ^3f}{\partial y^2 \partial x}& \frac{\partial ^3f}{\partial y^3}
\end{bmatrix}$

Since most of the terms are constant in second order Hessian, the only non zero third order partial derivative  is
$\frac{\partial ^3f}{\partial y^3} =6 \Rightarrow \frac{\partial ^3f}{\partial y^3}(1,2)=6$
All other derivatives will vanish
$D^3_{x,y}f[:,:,1]=\begin{bmatrix}0 & 0\\
0& 0
\end{bmatrix}$
$D^3_{x,y}f[:,:,2]=\begin{bmatrix}0 & 0\\
0& 6
\end{bmatrix}$
$\frac{D^3_{x,y}f(1,2)}{3!}\delta^3=(y-2)^3$

Overall, the exact Taylor series expansion of $f$ at $(x_0,y_0)=(1,2)$ is
$f(x,y)=f(1,2)+D^1_{x,y}f(1,2)\delta+\frac{D^2_{x,y}f(1,2)}{2!}\delta^2+\frac{D^3_{x,y}f(1,2)}{3!}\delta^3$

$=13+6(x-1)+14(y-2)+(x-1)^2+2(x-1)(y-2)+6(y-2)^2+(y-2)^3 $
$=13+6x-6+14y-28+x^2+1-2x+2xy-4x-2y+4+6y^2+24-24y+y^3-8+12y-6y^2 $
$=x^2+2xy+y^3+(6x-6x)+(14y-2y-24y+12y)+(13-6-28+1+4+24-8)$
$=x^2+2xy+y^3$

Find the second order Taylor series expansion for $f(x,y) = e^{-(x^2+y^2)} cos(xy)$ about $(0 , 0)$.

$f(0,0)=1$

First order partial derivatives
$\frac{\partial f}{\partial x}=-2xe^{-(x^2+y^2)}cos(xy)-ye^{-(x^2+y^2)}sin(xy)$
$\frac{\partial f}{\partial x}=-e^{-(x^2+y^2)}(2x.cos(xy)+y.sin(xy))$
$\frac{\partial f}{\partial x}(0,0)=0$

$\frac{\partial f}{\partial y}=-2ye^{-(x^2+y^2)}cos(xy)-xe^{-(x^2+y^2)}sin(xy)$
$\frac{\partial f}{\partial y}=-e^{-(x^2+y^2)}(2y.cos(xy)+x.sin(xy))$
$\frac{\partial f}{\partial y}(0,0)=0$
$D_{x,y}^1f(0,0)=\bigtriangledown_{x,y}f(0,0)=\left[ \frac{\partial f}{\partial x} \quad \frac{\partial f}{\partial y}\right]=[0 \quad 0] \in \mathbb{R}^{1 \times 2}$
$\frac{D_{x,y}^1f(0,0)}{1!}\delta=\left[0 \quad 0 \right]\begin{bmatrix}
x\\
y\end{bmatrix}=0$

The second order partial derivatives are given by
$\frac{\partial^2 f}{\partial x^2}=e^{-(x^2+y^2)}.2x(2x.cos(xy)+y.sin(xy))-e^{(x^2+y^2)}(2.cos(xy)-2xy.sin(xy)+y^2.cos(xy))$
$\frac{\partial^2 f}{\partial x^2}=e^{-(x^2+y^2)}((4x^2-y^2-2)cos(xy)+4xy.sin(xy))$
$\frac{\partial^2 f}{\partial x^2}(0,0)=-2$
similarly
$\frac{\partial^2 f}{\partial y^2}=e^{-(x^2+y^2)}((4xy.sin(xy)-(x^2-4y^2+2)cos(xy))$
$\frac{\partial^2 f}{\partial y^2}(0,0)=-2$

$\frac{\partial^2 f}{\partial x \partial y}=\frac{\partial^2 f}{\partial y \partial x}=e^{-(x^2+y^2)}((2x^2+2y^2-1)sin(xy)+3xy.cos(xy))$
$\frac{\partial^2 f}{\partial x \partial y}=\frac{\partial^2 f}{\partial y \partial x}(0,0)=0$
$\frac{D_{x,y}^2f(0,0)}{2!}\delta^2=\frac{1}{2}\left[x \quad y \right]\begin{bmatrix}
-2 & 0\\
0 & -2
\end{bmatrix}\begin{bmatrix}x\\
y\end{bmatrix}=-x^2-y^2$

the second degree Taylor polynomial at point (0,0) is
$f(0,0)+\frac{D_{x,y}^1f(0,0)}{1!}\delta+\frac{D_{x,y}^2f(0,0)}{2!}\delta^2$
$=1+0-x^2-y^2$
$=1-x^2-y^2$

Find the linear approximation to the function $f(x,y) = 2 - sin(-x -3y)$ at the point (0 , π), and then use your answer to estimate $f(0.001 , π)$.
$f(0,\pi)=2-sin(0-3\pi)=2+sin(3\pi)=2$
First order partial derivatives
$\frac{\partial f}{\partial x}=cos(-x-3y)$
$\frac{\partial f}{\partial x}(0,\pi)=cos(-3\pi)=-1$

$\frac{\partial f}{\partial y}=3cos(-x-3y)$
$\frac{\partial f}{\partial y}(0,\pi)=3.cos(-3\pi)=-3$
$\frac{D_{x,y}^1f(0,0)}{1!}\delta=\left[-1\quad -3 \right]\begin{bmatrix}
x\\
y-\pi\end{bmatrix}=-x-3y+3\pi$

Linear approximation at $(0,\pi)$ is
$f(0,\pi)+\frac{D_{x,y}^1f(0,0)}{1!}\delta$
$=2-x-3y+3\pi$
value at $f(0.001 , π)$ is
$2-0.001-3\pi+3\pi$
$=1.999$

Find the second order Taylor series expansion for $f(x, y) = (x + y)^2$ about $(0 , 0)$

$f(0,0)=0$

First order partial derivatives
$\frac{\partial f}{\partial x}=2(x+y)$
$\frac{\partial f}{\partial x}(0,0)=0$
$\frac{\partial f}{\partial y}=2(x+y)$
$\frac{\partial f}{\partial y}(0,0)=0$
$\frac{D_{x,y}^1f(0,0)}{1!}\delta=\left[0 \quad 0 \right]
\begin{bmatrix}
x\\
y
\end{bmatrix}=0$


Second order partial derivatives
$\frac{\partial^2 f}{\partial x^2}=2$
$\frac{\partial^2 f}{\partial x^2}(0,0)=2$
$\frac{\partial^2 f}{\partial y^2}=2$
$\frac{\partial^2 f}{\partial y^2}(0,0)=2$

$\frac{\partial^2 f}{\partial x \partial y}=2$
$\frac{\partial^2 f}{\partial x \partial y}(0,0)=2$
$\frac{\partial^2 f}{\partial y \partial x}=2$
$\frac{\partial^2 f}{\partial y\partial x}(0,0)=2$
$\frac{D_{x,y}^2f(0,0)}{2!}\delta^2=\frac{1}{2}\left[x \quad y \right]\begin{bmatrix}
2 & 2\\
2 & 2
\end{bmatrix}\begin{bmatrix}x\\
y\end{bmatrix}=x^2+2xy+y^2$

the second order Taylor series expansion about(0,0) is
$f(0,0)+\frac{D_{x,y}^1f(0,0)}{1!}\delta+\frac{D_{x,y}^2f(0,0)}{2!}\delta^2$
$=0+0+x^2+2xy+y^2$
$=x^2+2xy+y^2$

Compute the Taylor series expansion of $f(x,y)=x^2+2xy+y^3$ at $(x_0,y_0)=(1,1)$

$f(1,1)=4$
First order partial derivatives
$\frac{\partial f}{\partial x}=2x+2y$
$\frac{\partial f}{\partial x}(1,1)=4$
$\frac{\partial f}{\partial y}=2x+3y^2$
$\frac{\partial f}{\partial y}(1,1)=5$
$\frac{D_{x,y}^1f(1,1)}{1!}\delta=\left[4 \quad 5 \right]
\begin{bmatrix}
x-1\\
y-1
\end{bmatrix}=4x+5y-9$

Second order partial derivatives
$\frac{\partial^2 f}{\partial x^2}=2$
$\frac{\partial^2 f}{\partial x^2}(1,1)=2$
$\frac{\partial^2 f}{\partial y^2}=6y$
$\frac{\partial^2 f}{\partial y^2}(1,1)=6$

$\frac{\partial^2 f}{\partial x \partial y}=2$
$\frac{\partial^2 f}{\partial x \partial y}(1,1)=2$
$\frac{\partial^2 f}{\partial y \partial x}=2$
$\frac{\partial^2 f}{\partial y\partial x}(1,1)=2$

$\frac{D_{x,y}^2f(1,1)}{2!}\delta^2=\frac{1}{2}\left[x-1 \quad y-1 \right]\begin{bmatrix}
2 & 2\\
2 & 6
\end{bmatrix}
\begin{bmatrix}
x-1\\
y-1\end{bmatrix}=x^2+3y^2-4x-8y+2xy+6$

the second order Taylor series expansion about(1,1) is
$f(1,1)+\frac{D_{x,y}^1f(1,1)}{1!}\delta+\frac{D_{x,y}^2f(1,1)}{2!}\delta^2$
$=4+(4x+5y-9)+x^2+3y^2-4x-8y+2xy+6$
$=x^2+3y^2-3y+2xy+1$

Compute the Taylor series expansion of $f(x,y)=x^2y+3y-2$ at $(x_0,y_0)=(1,-2)$

$f(x,y)=x^2y+3y-2$
$f(1,-2)=-10$
First order partial derivatives
$\frac{\partial f}{\partial x}=2xy$
$\frac{\partial f}{\partial x}(1,-2)=-4$
$\frac{\partial f}{\partial y}=x^2+3$
$\frac{\partial f}{\partial y}(1,-2)=4$
$\frac{D_{x,y}^1f(1,1)}{1!}\delta=\left[-4 \quad 4 \right]
\begin{bmatrix}
x-1\\
y+2
\end{bmatrix}=-4x+4y+12$

Second order partial derivatives
$\frac{\partial^2 f}{\partial x^2}=2y$
$\frac{\partial^2 f}{\partial x^2}(1,-2)=-4$
$\frac{\partial^2 f}{\partial y^2}=0$
$\frac{\partial^2 f}{\partial y^2}(1,-2)=0$

$\frac{\partial^2 f}{\partial x \partial y}=2x$
$\frac{\partial^2 f}{\partial x \partial y}(1,-2)=2$
$\frac{\partial^2 f}{\partial y \partial x}=2x$
$\frac{\partial^2 f}{\partial y\partial x}(1,-2)=2$

$\frac{D_{x,y}^2f(1,-2)}{2!}\delta^2=\frac{1}{2}\left[x-1 \quad y+2 \right]\begin{bmatrix}
-4 & 2\\
2 & 0
\end{bmatrix}
\begin{bmatrix}
x-1\\
y+2\end{bmatrix}=-2x^2+12x-3y+4xy-8$

the second order Taylor series expansion about(1,-2) is
$f(1,-2)+\frac{D_{x,y}^1f(1,-2)}{1!}\delta+\frac{D_{x,y}^2f(1,-2)}{2!}\delta^2$
$=-10+(-4x+4y+12)-2x^2+12x-3y+4xy-8$
$=-2x^2+8x+y-6$

Comments

Popular posts from this blog

Mathematics for Machine Learning- CST 284 - KTU Minor Notes - Dr Binu V P

  Introduction About Me Syllabus Course Outcomes and Model Question Paper Question Paper July 2021 and evaluation scheme Question Paper June 2022 and evaluation scheme Overview of Machine Learning What is Machine Learning (video) Learn the Seven Steps in Machine Learning (video) Linear Algebra in Machine Learning Module I- Linear Algebra 1.Geometry of Linear Equations (video-Gilbert Strang) 2.Elimination with Matrices (video-Gilbert Strang) 3.Solving System of equations using Gauss Elimination Method 4.Row Echelon form and Reduced Row Echelon Form -Python Code 5.Solving system of equations Python code 6. Practice problems Gauss Elimination ( contact) 7.Finding Inverse using Gauss Jordan Elimination  (video) 8.Finding Inverse using Gauss Jordan Elimination-Python code Vectors in Machine Learning- Basics 9.Vector spaces and sub spaces 10.Linear Independence 11.Linear Independence, Basis and Dimension (video) 12.Generating set basis and span 13.Rank of a Matrix 14.Linear Mapping and Matri

1.1 Solving system of equations using Gauss Elimination Method

Elementary Transformations Key to solving a system of linear equations are elementary transformations that keep the solution set the same, but that transform the equation system into a simpler form: Exchange of two equations (rows in the matrix representing the system of equations) Multiplication of an equation (row) with a constant  Addition of two equations (rows) Add a scalar multiple of one row to the other. Row Echelon Form A matrix is in row-echelon form if All rows that contain only zeros are at the bottom of the matrix; correspondingly,all rows that contain at least one nonzero element are on top of rows that contain only zeros. Looking at nonzero rows only, the first nonzero number from the left pivot (also called the pivot or the leading coefficient) is always strictly to the right of the  pivot of the row above it. The row-echelon form is where the leading (first non-zero) entry of each row has only zeroes below it. These leading entries are called pivots Example: $\begin

4.3 Sum Rule, Product Rule, and Bayes’ Theorem

 We think of probability theory as an extension to logical reasoning Probabilistic modeling  provides a principled foundation for designing machine learning methods. Once we have defined probability distributions corresponding to the uncertainties of the data and our problem, it turns out that there are only two fundamental rules, the sum rule and the product rule. Let $p(x,y)$ is the joint distribution of the two random variables $x, y$. The distributions $p(x)$ and $p(y)$ are the corresponding marginal distributions, and $p(y |x)$ is the conditional distribution of $y$ given $x$. Sum Rule The addition rule states the probability of two events is the sum of the probability that either will happen minus the probability that both will happen. The addition rule is: $P(A∪B)=P(A)+P(B)−P(A∩B)$ Suppose $A$ and $B$ are disjoint, their intersection is empty. Then the probability of their intersection is zero. In symbols:  $P(A∩B)=0$  The addition law then simplifies to: $P(A∪B)=P(A)+P(B)$  wh